Reconstructing the Legal Enforcement Framework for Digital Activism in an Era of Technological Disruption - Nibrosu Rohid; Rahma Sugihartati; Bagong Suyanto; Oleksandr Gotin; Nabrisi Rohid; Sukisno (Nusantara: Journal of Law Studies, 2026)
The rapid expansion of digital technologies has transformed civic engagement by enabling digital activism as a powerful medium for public participation, social advocacy, and democratic expression. While these developments strengthen citizen engagement, they also create significant legal challenges in balancing freedom of expression with the need to maintain public order and prevent digital misconduct. This study reconstructs the legal enforcement framework governing digital activism in the era of technological disruption by identifying regulatory deficiencies, evaluating current enforcement practices, and proposing a more adaptive and rights-based legal model. The research employs a qualitative normative legal methodology complemented by a socio-legal perspective. It analyzes statutory regulations, legal doctrines, judicial decisions, and policy frameworks concerning digital expression and online activism. Data were collected through a systematic review of legal documents, scholarly literature, and policy reports, then examined using conceptual and comparative legal analysis to identify structural weaknesses within existing enforcement mechanisms. The findings demonstrate that current enforcement remains largely rooted in conventional regulatory paradigms that inadequately address the complexity of digital activism. Ambiguous legal provisions, overlapping institutional authorities, and inconsistent enforcement practices generate legal uncertainty and increase the risk of over-criminalizing legitimate civic expression. Furthermore, the absence of clear legal standards governing digital advocacy, online mobilization, and algorithm-driven information dissemination complicates effective enforcement and weakens legal certainty. This study proposes a reconstructed enforcement framework grounded in the principles of proportionality, transparency, accountability, and digital rights protection. The framework emphasizes adaptive regulation, integrated digital governance, institutional capacity building, and clearer legal standards for technology-mediated civic participation. By bridging technological realities with constitutional safeguards, the proposed model contributes to contemporary legal scholarship on digital governance while offering practical policy recommendations for developing a more balanced, accountable, and responsive legal system capable of addressing the evolving challenges of the digital era.